Lampung Krakatau Festival: Tourism Development and Active Citizens Participation to Strengthen Community Civic Virtue - Muhammad Mona Adha; Budimansyah Dasim; Arief Nugroho; Mitchell Mollison (Indonesian Journal of Tourism and Leisure, 2021)
The tourism sector must be able to involve the community through space in order to gather, interact and communicate. Krakatau Festival as a medium that involves the participation of individuals and the community can support the development of tourism in Lampung Province. The community engagement in the festival is responsible as citizens of the community including the government, stakeholders, people, communities to take part actively and create strong social interrelation and cohesion. Tourism development through the community as part of sapta pesona is the main focus supported by a variety of cultural activities, destinations, and ultimately creates social cohesion as part of the civilization of citizenship. Qualitative research with ethnographic methods is implemented to get data and information comprehensively from various sources. The results of the study found that the context of the Krakatau Festival activities in real terms has the potential to increase tourism with historical values of Krakatau and can unite the community in a positive social interaction relationship and strengthen the active participation of local community virtue.